2016
DOI: 10.1111/aos.13339
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of posterior vitreous detachment in glaucoma patients and controls

Abstract: Our results suggest that the presence or absence of PVD might be a valuable hint for diagnosing glaucoma - however, further research is needed to determine whether PVD can be used to supplement current glaucoma screening guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
2
10
3
Order By: Relevance
“…In contrast to the recent published findings of Schwab et al. () who reported glaucoma patients to experience PVD at younger age compared to healthy controls, our results indicate the opposite. However, there seem to be significant differences in the methodology of PVD stage grading as Schwab et al.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to the recent published findings of Schwab et al. () who reported glaucoma patients to experience PVD at younger age compared to healthy controls, our results indicate the opposite. However, there seem to be significant differences in the methodology of PVD stage grading as Schwab et al.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, a stage 2 PVD was never seen in our study subjects as there was always, although sometimes minimal, separation present of the posterior hyaloid and ILM nasal to the optic disc when there was a concomitant perimacular PVD. In contrast to the recent published findings of Schwab et al (2017) who reported glaucoma patients to experience PVD at younger age compared to healthy controls, our results indicate the opposite. However, there seem to be significant differences in the methodology of PVD stage grading as Schwab et al discriminated between 'initial PVD' which is to be regarded as a PVD stage 1 and 'advanced PVD' which could be PVD stage 2, 3 or 4.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Thereby, aqueous humor outflow resistance and increased intraocular pressure (IOP) increase, facilitating the clinical onset of glaucoma and supporting the hypothesis that oxidative stress is an important factor in open-angle glaucoma [10,14]. Recently, the observation that glaucoma is linked to premature posterior vitreous detachment (PVD) has led to the hypothesis that ROS, which appear increased in glaucoma, might also lead to changes of the vitreous [15]. However, the impact of glaucomatous oxidative stress on the vitreous has not been investigated yet.…”
Section: Introductionmentioning
confidence: 93%
“…Collagen opacities, which are common in glaucoma, 28  may cause shadow effect by blocking the return of the illumination light from the retina. 29  The shadow effect results in an OCT image and vessel density values which falsely imitate reduced or missing perfusion (Figure 5).…”
Section: Image Quality and Artifacts In Optical Coherence Tomography mentioning
confidence: 99%